MEDIA MASSA DAN KONSTRUKSI GAYA HIDUP PEREMPUAN - Tuti Andriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
There are three reasons why woman represents the interesting market target. First, woman is a directly consumer, second, woman represents a super persuader in her family, third, woman is the future consumer (a potential consumer candidate). Expense by exploiting the free time and conservancy of body (always remain to be beautiful) representing the cultural characteristic of consumer always will be there and pumped by mass media to audience continuously. In this case, television has constructed a life style which finally influence woman. The effect of the life style which created by television to the woman is the woman behavior tends oward the consumptive life style and assumes that the appearance is its without thinking of the real situation. This article discusses how does the mass media construct the social reality of human being especially woman.